THE INFLUENCE OF HIGHER ORDER THINKING SKILLS (HOTS) LEARNING MODEL AND LEARNING MOTIVATION ON ACHIEVEMENT IN LEARNING ISLAMIC CULTURAL HISTORY - Mahmud Yunus (Tadibia Islamika, 2021)
The objectives to be achieved in the discussion of this tesi are 1. To analyze the effect of the HOTS learning model on the learning achievement of SKI subject at MIN 2 Pemalang, 2. To analyze the effect of learning motivation on learning achievement of SKI subject at MIN 2 Pemalang, 3. To analyze the effect HOTS learning model and learning motivation towards learning achievement of SKI subjects at MIN 2 Pemalang. This type of research is quantitative research with a quasi experimental approach. The population in this study were students of class V.B and class V students in MIN 2 Pemalang academic year 2019/2020. The data is collected through a questionare instrument of learning motivation variables and also the results of student tests as a variable of student achievement. The results of the data are processed through statistical calculations and the average correlation, obtained through the use of SPSS 21.0. Data analysis using t-test with a significance level. The results of this study are as follows: 1) There is a significant influence on the HOTS learning model on the learning achievement of SKI subjects. 2) There is a significant influence on the learning motivation learning achievement of SKI subjects. 3) There is a significant influence on the HOTS learning model and learning motivation on SKI subject learning achievement.